The Impact of Environmental Knowledge on Food Waste Reduction and Sustainability Practices among Hospitality Students in Malaysia - Rani, Zaharah Mohamed; Ismail, Anida; Rahim, Noraini; Apandi, Siti Rohimi Mohamed; Farook, Ferial (Information Management and Business Review, 2024)
Environmental sustainability and food waste reduction are among the critical challenges facing the hospitality industry worldwide. This study was conducted to identify the impact of environmental knowledge on food waste reduction and sustainability practices among hospitality students in Malaysia. A quantitative approach was used, and we surveyed 94 hospitality students from various programs at UiTM Penang. The online questionnaire was conducted and analyzed using Pearson correlation and multiple regression analysis. There is a significant positive correlation between environmental knowledge, food waste behaviors and sustainability-related behaviors. The strongest relationship was found between food waste behaviors and sustainability-related behaviors, suggesting that environmental knowledge and food waste practices are closely related to broader sustainability behaviors in hospitality education. The study contributes to the understanding of how environmental education can shape the future of hospitality professional practice, offering valuable insights for the development of industry curricula and training programs aimed at promoting sustainable practices in the hospitality sector.